Establish The Sustainability of Village Traditions that Have Been Lost by Holding The Tenong Festival in Bogeman Village, Magelang, Indonesia - Dewi, Kun Arsanti; Fatmawati, Nurida; Sukadi, Sukadi; Harismah, Kun (Universitas Komputer Indonesia, 2025)
Kampung Bogemen (Bogeman Village) is one of the old villages in Magelang Municipality. The village name was taken from the name of Mbah Bogem, who was the first village head in the village around the 1800s. As an old village, there should be many relics of village life traditions. However, in line with modern life, many of these traditions are gradually disappearing. Facing this condition, the Bogeman Village Community was trying to revive the traditions of its people by holding a Tenong Festival which was held at the Habitat Park. Kampung Bogeman was previously a slum because the handling of residential infrastructure was not managed properly. In 2019, assistance was received from the Central Java Province Government in the form of repairs and development of residential infrastructure, including repairs and development of Habitat Parks, making Kampung Bogeman a village free from slums in 2022. This study is intended to examine how big the positive impact is on efforts to sustain traditional village life in Bogeman village through the Tenong Festival activities. The research method used is a qualitative research method carried out through interviews and collecting existing data in order to exploit all conditions and presented in detail to obtain the positive impacts felt by the Bogeman Village Community, so that from the positive impacts obtained, it is hoped that similar festivals will be imitated by other villages in order to re-grow the sustainability of village life traditions. Keywords: Kampung Bogeman, Tenong Festival, Habitat, Slum, Village Community